Kajian Aktivitas Pedagang Kaki Lima di Ruang Publik Kawasan Simpang Lima Pati - Taufik, Muhamat (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Street vendors in Pati Simpang Lima area are invading urban public spaces with increasing number. While providing job opportunities, their unregulated existence reduces the level of service of the public spaces and has starting to create environmental problems. The study examines the street vendorsâ€™ activity characteristics, space and infrastructure availability, seller and customer preference and the local governmentâ€™s policy on street vendors. The study identified that the availability of open public space in Pati Simpang Lima area have attracted the increase of street vendor activities. There is a growing need for infrastructure such as parking spaces, public toilets and waste related infrastructure. There has not been any local government regulation let alone innovative approaches to street vendor activities in either socioâ€cultural, economic nor normative terms. The direction was to physically regulate the street vendor area in terms of vendor space allocation, business times regulations and infrastructure. The lack of space in the area has imposed a need for relocation for some of the vendors to a new place such as Jalan Penjawi, with adequate supply of infrastructure. In terms of policy, there should be legalization and limitation of the number of street vendors using socioâ€cultural, economic and normative models.